Analisis Peran Energi Terbarukan, Inflasi, Ekspor, Dan Manufaktur Terhadap GNI Per Kapita Dalam Upaya Menghindari Middle-Income Trap Di Indonesia - I Made Renaldi; I Wayan Suparta (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of renewable energy, inflation, manufacturing value added, and exports on Gross National Income (GNI) per capita in Indonesia as part of the effort to escape the middle-income trap. The study uses annual time series data from 1987 to 2023 and applies the Vector Error Correction Model (VECM) for analysis. The long-term estimation results show that renewable energy and manufacturing value added have a positive and significant effect on GNI per capita, while inflation has a negative and significant effect. Exports show a positive but statistically insignificant effect, likely due to the dominance of commodity-based exports. In the short term, renewable energy has a consistently positive and significant effect across all lags. Inflation has a significant negative effect only in the first lag, while exports show a negative effect in the second lag. Manufacturing value added does not have a significant short-term effect. The significant error correction coefficient (CointEq1) of -0.879844 indicates a strong adjustment mechanism, suggesting that the model tends to return to long-term equilibrium rapidly after short-term shocks. These findings suggest that clean energy transition, strengthening of the manufacturing sector, and inflation control are strategic factors in increasing national income and avoiding the middle-income trap.